Relevance of genetics for conservation policies: the case of Minorcan cork oaks - Lorenzo, Zaida; Burgarella, Concetta; de Heredia, Unai López; Lumaret, Roselyne; Petit, Rémy J; Soto, Álvaro; Gil, Luis; Soto, Álvaro; Gil, Luis (Annals of Botany, 2009)
Background and Aims Marginal populations of widely distributed species can be of high conservation interest when they hold a significant or unique portion of the genetic diversity of the species. However, such genetic information is frequently lacking. Here the relevance of genetic surveys to develop efficient conservation strategies for such populations is illustrated using cork oak (Quercus suber) from Minorca (Balearic Islands, Spain) as a case study. Cork oak is highly endangered on the island, where no more than 67 individuals live in small, isolated stands in siliceous sites. As a consequence, it was recently granted protected status.Methods Two Bayesian clustering approaches were used to analyse the genetic structure of the Minorcan population, on the basis of nuclear microsatellite data. The different groups within the island were also compared with additional island and continental populations surrounding Minorca.Key Results Very high genetic diversity was found, with values comparable with those observed in continental parts of the species' range. Furthermore, the Minorcan oak stands were highly differentiated from one another and were genetically related to different continental populations of France and Spain.Conclusions The high levels of genetic diversity and inter-stands differentiation make Minorcan cork oak eligible for specific conservation efforts. The relationship of Minorcan stands to different continental populations in France and Spain probably reflects multiple colonization events. However, discrepancy between chloroplast DNA- and nuclear DNA-based groups does not support a simple scenario of recent introduction. Gene exchanges between neighbouring cork oak stands and with holm oak have created specific and exceptional genetic combinations. They also constitute a wide range of potential genetic resources for research on adaptation to new environmental conditions. Conservation guidelines that take into account these findings are provided.
From Duplicate 2 (Relevance of genetics for conservation policies: the case of Minorcan cork oaks - Lorenzo, Zaida; Burgarella, Concetta; de Heredia, Unai López; Lumaret, Roselyne; Petit, Rémy J; Soto, Álvaro; Gil, Luis)
Keywords: Balearic Islands; cluster analysis; conservation guidelines; Conservation of Natural Resources; Genetic Variation; Geography; marginal populations; Minorca; Nuclear microsatellites; Population Dynamics; Q. ilex (holm oak); Quercus; Quercus suber (cork oak); Quercus: genetics; Soil; Spain; western Mediterranean

Relevance of genetics for conservation policies: the case of Minorcan cork oaks - Lorenzo, Zaida; Burgarella, Concetta; de Heredia, Unai López; Lumaret, Roselyne; Petit, Rémy J.; Soto, Álvaro; Gil, Luis; Soto, Álvaro; Gil, Luis (Annals of Botany, 2009)
Background and Aims Marginal populations of widely distributed species can be of high conservation interest when they hold a significant or unique portion of the genetic diversity of the species. However, such genetic information is frequently lacking. Here the relevance of genetic surveys to develop efficient conservation strategies for such populations is illustrated using cork oak (Quercus suber) from Minorca (Balearic Islands, Spain) as a case study. Cork oak is highly endangered on the island, where no more than 67 individuals live in small, isolated stands in siliceous sites. As a consequence, it was recently granted protected status.Methods Two Bayesian clustering approaches were used to analyse the genetic structure of the Minorcan population, on the basis of nuclear microsatellite data. The different groups within the island were also compared with additional island and continental populations surrounding Minorca.Key Results Very high genetic diversity was found, with values comparable with those observed in continental parts of the species' range. Furthermore, the Minorcan oak stands were highly differentiated from one another and were genetically related to different continental populations of France and Spain.Conclusions The high levels of genetic diversity and inter-stands differentiation make Minorcan cork oak eligible for specific conservation efforts. The relationship of Minorcan stands to different continental populations in France and Spain probably reflects multiple colonization events. However, discrepancy between chloroplast DNA- and nuclear DNA-based groups does not support a simple scenario of recent introduction. Gene exchanges between neighbouring cork oak stands and with holm oak have created specific and exceptional genetic combinations. They also constitute a wide range of potential genetic resources for research on adaptation to new environmental conditions. Conservation guidelines that take into account these findings are provided.
From Duplicate 2 (Relevance of genetics for conservation policies: the case of Minorcan cork oaks - Lorenzo, Zaida; Burgarella, Concetta; de Heredia, Unai López; Lumaret, Roselyne; Petit, Rémy J; Soto, Álvaro; Gil, Luis)From Duplicate 2 (Relevance of genetics for conservation policies: the case of Minorcan cork oaks - Lorenzo, Zaida; Burgarella, Concetta; de Heredia, Unai López; Lumaret, Roselyne; Petit, Rémy J; Soto, Álvaro; Gil, Luis)The following values have no corresponding Zotero field: accession-num: 19671575
Keywords: Balearic Islands; cluster analysis; conservation guidelines; Conservation of Natural Resources; Genetic Variation; Geography; marginal populations; Minorca; Nuclear microsatellites; Population Dynamics; Q. ilex (holm oak); Quercus; Quercus suber (cork oak); Quercus: genetics; Soil; Spain; western Mediterranean

The influence of linear elements on plant species diversity of Mediterranean rural landscapes: assessment of different indices and statistical approaches. - García del Barrio, J M; Ortega, M; Vázquez De la Cueva, A; Elena-Rosselló, R (Environmental monitoring and assessment, 2006)
This paper mainly aims to study the linear element influence on the estimation of vascular plant species diversity in five Mediterranean landscapes modeled as land cover patch mosaics. These landscapes have several core habitats and a different set of linear elements--habitat edges or ecotones, roads or railways, rivers, streams and hedgerows on farm land--whose plant composition were examined. Secondly, it aims to check plant diversity estimation in Mediterranean landscapes using parametric and non-parametric procedures, with two indices: Species richness and Shannon index. Land cover types and landscape linear elements were identified from aerial photographs. Their spatial information was processed using GIS techniques. Field plots were selected using a stratified sampling design according to relieve and tree density of each habitat type. A 50x20 m2 multi-scale sampling plot was designed for the core habitats and across the main landscape linear elements. Richness and diversity of plant species were estimated by comparing the observed field data to ICE (Incidence-based Coverage Estimator) and ACE (Abundance-based Coverage Estimator) non-parametric estimators. The species density, percentage of unique species, and alpha diversity per plot were significantly higher (p < 0.05) in linear elements than in core habitats. ICE estimate of number of species was 32% higher than of ACE estimate, which did not differ significantly from the observed values. Accumulated species richness in core habitats together with linear elements, were significantly higher than those recorded only in the core habitats in all the landscapes. Conversely, Shannon diversity index did not show significant differences.
Keywords: Biodiversity; Conservation of Natural Resources; Conservation of Natural Resources: statistics & nu; core habitat; diversity; Ecosystem; ecotones; Environmental Monitoring; Environmental Monitoring: methods; Geography; landscape; linear elements; Mediterranean; Mediterranean Region; Plant Development; Poaceae; Poaceae: growth & development; Shannon index; Species richness; Species Specificity; Trees; Trees: growth & development

Folk phytotherapeutical plants from Maratea area (Basilicata, Italy). - Guarrera, Paolo Maria; Salerno, Giovanni; Caneva, Giulia (Journal of ethnopharmacology, 2005)
Field ethnobotanical survey was undertaken for the period of 2002-2003 in the Tyrrhenian part of the Basilicata region of southern Italy. Data of 56 species of plants belonging to 29 families where gathered through interviews; among the species, 47 are used in human therapy, 6 as insect repellents, 15 in veterinary medicine, 1 for its ichthyotoxic properties and 3 for magic therapeutic purposes. The most important findings in ethnomedicine relate to Nasturtium officinale (renal colic, liver diseases), Foeniculum vulgare subsp. piperitum (mouth ulcers), Leopoldia comosa (toothache, headache), Micromeria graeca subsp. graeca (coughs) and Ceterach officinarum (malaria), while in the ethnoveterinary field, we have Pteridium aquilinum (wolf bites) and Spartium junceum (fractures of animal limbs).
Keywords: Abdominal Pain; Abdominal Pain: drug therapy; Anthelmintics; Anthelmintics: therapeutic use; Antiparasitic plants; Basilicata; Common Cold; Common Cold: drug therapy; Cough; Cough: drug therapy; Diuretics; Diuretics: chemistry; Diuretics: therapeutic use; Ethnobotany; Ethnopharmacology; Ethnopharmacology: methods; Furunculosis; Furunculosis: drug therapy; Geography; Humans; Italy; Lung Diseases; Lung Diseases: drug therapy; Medicinal; Medicinal plants; Medicinal: classification; Medicine; Phytotherapy; Plant Preparations; Plant Preparations: therapeutic use; Plants; Skin Diseases; Skin Diseases: drug therapy; Time Factors; Traditional; Veterinary plants; Wound Healing; Wound Healing: drug effects; Wounds and Injuries; Wounds and Injuries: drug therapy